Exploring services science Second International Conference, IESS 2011, Geneva, Switzerland, February 16-18, 2011, Revised Selected Papers - Rimondini, Michela; Snene,Mehdi; Ralyté,Jolita; Morin, Jean-Henry (Springer, 2011)
This book contains the refereed proceedings of the Second International Conference on Exploring Services Science (IESS) that was held in Geneva, Switzerland, in February 2010.Based on the previous edition and the momentum in this emerging and exciting field, IESS 2011 offered academics, researchers, and practitioners from various disciplines an exploratory platform to communicate and share their results and experiences. The 17 full and 2 short papers accepted for IESS were selected from 47 submissions and cover the whole life cylce of service development (including service innovation, service design, service composition, and service sustainability) as well as the application of services in information technology, businesses, and public administration.